Analisis Penyebab Defect Untuk Mencegah Defect Berulang Dengan Metode FMEA Pada Produk Televisi Di PT. FGH - Akhsani Nur Amalia; Anwar Maulana (Fakultas Teknik Universitas Tulang Bawang, 2023)
FGH is a manufacturing company engaged in television assembly. In the process, there is a product defect. In order to avoid repeated defects, this research tries to analyze the factors that cause the current defects. After classification using the Pareto diagram, four types of defects are obtained that need to be repaired immediately. These defects are scratch screens, gaps, light leakage and foreign materials. Further analysis was carried out on each type of defect. With the FMEA method, the results of the analysis show that PT. FGH must check the materials used before the process is carried out, ensure that the work methods are well realized and provide instructions for using tools and machines so that the output is as expected. Keywords: Analysis, Defect, FMEA, Pareto